Influence of Career Needs in Psychological Contract on Job Burnout - Ekore, John Oselenbalu (Journal of Posthumanism, 2025)
The well-adjusted employee is better prepared to promote productive work outcomes. Among factors that have been found in adjustment, employee needs and their experiences on the job are salient. In the Middle East, there is dearth of literature that considered aviation employees’ career concerns in psychological contract and job burnout in the aviation industry. Hence, the cross-sectional survey with questionnaires for data collection. They contain the career needs and the adapted Maslach (1996) burnout scales in a sample of 1051 respondents. Findings indicated significant prediction of burnout by career needs (R2 = 0.28, F=99, p<.001). Sustainability need, career stability, and development need significantly predicted job burnout (career sustainability need, β= -0.20, t= -6.88, p<.001; career stability, β =-0.49, t = -16.57, p<.001; development need, β= 0.14, t = 4.82, p<.001) respectively. Work-life balance was not a significant predictor (β= -0.02, t= -0.75, ns). It was concluded that the identified career needs are significant factors in employees’ perception of job burnout. The outcome necessitated the suggestion to incorporate career needs as components of employees’ psychological contract when planning burnout interventions in the industry